Mattoso Câmara : uma experiência de divulgação científica da linguística do/no Brasil - Boschilia, Camila Cristina (2017)
This Masters dissertation proposes a study of the linguist Joaquim Mattoso Câmara Júnior, concentrating on the researcher's figure as science communicator. For this study we start from the reflection of language as divulgation object, addressing concepts of the dissemination, didactization and publicity, supported in studies of the authors Jacqueline Authier-Revuz and Eni Orlandi about scientific divulgation discourse. For the realization of this approach, we discuss the relationship between enunciator and enunciatee and the enunciative strategies present in textualization process as proposed by Semiotics Discourse. We have established as analysis corpus the researcher's scientific divulgation texts published in the newspaper Correio da Manhã in 1934 and in the magazine A Cigarra Magazine between the years 1957-1960. We intend to draw attention to the importance of dissemination of linguistic science of/in Brazil, encouraging the realization of science disseminators activities at present, contribute to research on the language, especially when it comes to divulgation object and intellectual productions of the researche, besides discuss about the actuality of the initiative of researcher, since it is still evident the need for divulgation of linguistic science and, together, the making of their professional, the linguist, and its value and recognition to various areas of human activity in society.